2016
DOI: 10.1093/abbs/gmv135
|View full text |Cite
|
Sign up to set email alerts
|

The involvement of <italic>N</italic>-methyl-d-aspartate receptor (NMDAR) subunit NR1 in the pathophysiology of schizophrenia

Abstract: Schizophrenia is a severe mental illness that afflicts nearly 1% of the world population. Although the exact pathophysiology of schizophrenia is unknown, the N-methyl-D-aspartate receptor (NMDAR), a major glutamate receptor subtype, has received great attention. The NR1 subunit is often considered indispensable for functional NMDAR assemblies, abnormal modulation of which is found in patients with schizophrenia. In this review, we discuss how disrupted function of NR1 subunits in NMDAR leads to the progression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 132 publications
0
27
0
Order By: Relevance
“…Recent advances in genetic, preclinical and clinical pharmacological, and brain studies have shown the role of disrupted NMDAR-NR1 subunit-mediated glutamatergic pathways in schizophrenia [6]. Psychosis is a canonical symptom of anti-NMDAR encephalitis.…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in genetic, preclinical and clinical pharmacological, and brain studies have shown the role of disrupted NMDAR-NR1 subunit-mediated glutamatergic pathways in schizophrenia [6]. Psychosis is a canonical symptom of anti-NMDAR encephalitis.…”
Section: Discussionmentioning
confidence: 99%
“…Glutamate activation of the NMDA receptor requires concurrent binding of glycine or, predominantly in the PFC, Dserine at the glycine modulatory site [6][7][8]. Thus, pharmacological modulation of the glycine site has been prioritised to restore hypofunction by direct agonism, inhibition of enzymes regulating serine metabolism or increasing synaptic glycine by inhibition of glycine transporters [9][10][11][12]. Although glycine and Dserine have been extensively characterised, it has proven very hard to generate small molecule, positive modulators of the glycine site.…”
Section: Introductionmentioning
confidence: 99%
“…30 NR1-knockdown rats also exhibited hyperlocomotion. 31 Based on these prior findings, we speculate that hyperlocomotion may be related to reduced NR1 expression in specific brain regions. Inhibitory synaptic transmission mediated by interneurons has a modulatory role in visceral pain.…”
Section: Discussionmentioning
confidence: 63%